Bilingualism and environment: from childhood to adulthood - Di Biase, Bruno; Qi, Ruying; Mohamed Salleh, Rabiah Tul Adawiyah (2020)
The talk explores the relationship between how children acquire several languages and their linguistic environmental factors.